The "Book of Mormon" a Biography. - Gutjahr, Paul C. (Princeton : Princeton University Press, 2012)
Late one night in 1823 Joseph Smith, Jr., was reportedly visited in his family's farmhouse in upstate New York by an angel named Moroni. According to Smith, Moroni told him of a buried stack of gold plates that were inscribed with a history of the Americas' ancient peoples, and which would restore the pure Gospel message as Jesus had delivered it to them. Thus began the unlikely career of the Book of Mormon, the founding text of the Mormon religion, and perhaps the most important sacred text ever to originate in the United States. Here Paul Gutjahr traces the life of this book as it has formed.
No; p; q; r; s; t; u; v; w; y; z.
Description based on print version record.
Keywords: Book of Mormon -- Criticism, interpretation, etc; Book of Mormon -- History; Religion; Book of Mormon -- History; Book of Mormon -- Criticism, interpretation, etc; RELIGION / Christianity / Church of Jesus Christ of Latter-day Saints (Mormon); Electronic books